2018
DOI: 10.3389/fonc.2018.00591
|View full text |Cite
|
Sign up to set email alerts
|

Delineating WWOX Protein Interactome by Tandem Affinity Purification-Mass Spectrometry: Identification of Top Interactors and Key Metabolic Pathways Involved

Abstract: It has become clear from multiple studies that WWOX (WW domain-containing oxidoreductase) operates as a “non-classical” tumor suppressor of significant relevance in cancer progression. Additionally, WWOX has been recognized for its role in a much wider array of human pathologies including metabolic conditions and central nervous system related syndromes. A myriad of putative functional roles has been attributed to WWOX mostly through the identification of various binding proteins. However, the reality is that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 56 publications
(89 reference statements)
0
39
1
Order By: Relevance
“…In fact, another study has shown via MS that WWOX and SCAMP3 co-immunoprecipitate, further emphasizing a possible functional role for this interaction. 56 CDC5L, cell division cycle 5-like, is a pre-mRNA splicing factor that is known to regulate mitotic progression. One study reported that depletion of CDC5L causes dramatic mitotic arrest, chromosome misalignment and sustained activation of the spindle assembly checkpoint, which eventually leads to mitotic catastrophe.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, another study has shown via MS that WWOX and SCAMP3 co-immunoprecipitate, further emphasizing a possible functional role for this interaction. 56 CDC5L, cell division cycle 5-like, is a pre-mRNA splicing factor that is known to regulate mitotic progression. One study reported that depletion of CDC5L causes dramatic mitotic arrest, chromosome misalignment and sustained activation of the spindle assembly checkpoint, which eventually leads to mitotic catastrophe.…”
Section: Discussionmentioning
confidence: 99%
“…Pathway analysis of identified WWOX binding proteins also confirmed its important role in metabolic pathways, setting it as one of the main regulators of glycolysis, fatty acid degradation, TCA cycle, de novo synthesis of lipids and amino acids. 26 …”
Section: Introductionmentioning
confidence: 99%
“… 16 , 20 , 21 , 41 , 42 Noteworthy, Dvl1 and Dvl2, core components of WNT pathway, were amongst the highest confidence protein interactors identified in TAP-MS WWOX protein interactome study. 26 …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, WWOX gene is one of the 5 recently discovered risk factors in Alzheimer’s disease 8 . WWOX interacts with specific cytosolic proteins, mainly functioning in normal cell physiology and death 15 and metabolism such as glycolysis, fatty acid degradation and acetyl-CoA generation 9 .…”
Section: Introductionmentioning
confidence: 99%